Gender–Caste Hegemony and Victimhood: A Study on Untouchable and The God of Small Things - Roy, Romeena; Jose, Antony (South Asian Journal of Social Sciences and Humanities, 2023)
India is distinctive for its varied cultures, enticing landscapes, and rich heritage. Intriguingly, caste and gender inequities are still pervasive in Indian society, and the recent financial crisis has given some millionaires a pretext to abuse their power by denying minority groups access to basic freedoms. Gender stereotypes are deeply ingrained in cultural and societal expectations, frequently harming people who don't fit the strict binary gender norms imposed by these institutions. People are classified into castes based on their social standing, class, and place of birth, and their caste status is determined by their largely unchanging familial origins. Both the Indian novels, Untouchable of Mulk Raj Anand which was published in 1935 and The God of Small Things by Arundhati Roy which was published 62 years after the first one display the interconnected and hegemonic nature of Caste and Gender. This paper analyses the interconnected and hegemonic nature of Caste and Gender and interrogates how the hegemony leads to victimhood as narrated by the novels Untouchable and The God of Small Things.
Keywords: Gender; Caste; Hegemony; Victimhood; Culture; Untouchability